2018
DOI: 10.1080/15412555.2019.1566893
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Provision for Patients with Advanced Chronic Obstructive Pulmonary Disease: A Systematic Integrative Literature Review

Abstract: Although chronic obstructive pulmonary disease (COPD) is recognized as being a life-limiting condition with palliative care needs, palliative care provision is seldom implemented. The disease unpredictability, the misconceptions about palliative care being only for people with cancer, and only relevant in the last days of life, prevent a timely integrated care plan. This systematic review aimed to explore how palliative care is provided in advanced COPD and to identify elements defining integrated palliative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…31 Palliative care services are designed to deliver multiprofessional care, while managing multidimensional complexity and they could play a role in the development of a care network for patients with advanced COPD. 32 Awareness about palliative care and its role in care delivery of patients with advanced COPD was lacking. None of the participants reported that healthcare services provided them with information about palliative care, the ones who were informed gathered their knowledge through their social network.…”
Section: Discussionmentioning
confidence: 99%
“…31 Palliative care services are designed to deliver multiprofessional care, while managing multidimensional complexity and they could play a role in the development of a care network for patients with advanced COPD. 32 Awareness about palliative care and its role in care delivery of patients with advanced COPD was lacking. None of the participants reported that healthcare services provided them with information about palliative care, the ones who were informed gathered their knowledge through their social network.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies brought a basic taxonomy of palliative care in advanced COPD [27]. Still, some unresolved issues remain and need to be addressed if palliative care is to be standardised and widely recommended [7,15,19].…”
Section: Resultsmentioning
confidence: 99%
“…33 This study was supported by a systematic review of the literature performed prior to the current research. The review identified a taxonomy involving different levels of care provision, where integrated care is the last step of a dynamic process of care delivery 16 . These results helped to raise awareness within the CIG about organisational changes that are necessary to develop integrated care.…”
Section: Discussionmentioning
confidence: 99%
“…15 A systematic review of the literature on palliative care integration in advanced COPD performed prior to this study, underlined the importance of organisational changes that are necessary to develop integrated care. 16 This helped to focus the research aim on how to identify practices designed to increase palliative care integration for patients with advanced COPD in a respiratory service in Southern Switzerland through a participatory action research approach, supported by a ToC framework.…”
Section: Introductionmentioning
confidence: 99%